Assessment of Insulin-related Knowledge among Healthcare Professionals in a Large Teaching Hospital in the United Kingdom - Amie Bain; Sallianne Kavanagh; Sinead McCarthy; Zaheer- (MDPI AG, 2019)
Despite numerous strategies introduced to promote the safe use of insulin, insulin-related medication errors persist. Our aim was to examine the knowledge and self-reported confidence of a range of healthcare professionals regarding insulin use in a large teaching hospital in the North of England. A 16-item electronic questionnaire was prepared in light of locally reported insulin-related incidents and distributed electronically to all healthcare professionals at the hospital over a 4-week study period. A range of healthcare professionals, including nurses, pharmacists, pharmacy technicians, junior doctors and consultants, completed the questionnaires (n = 109). Pharmacists achieved the greatest percentage of mean correct answers overall (49%), followed by consultant doctors (38%) and pharmacy technicians (37%), junior doctors (34%) and nurses (32%). Healthcare professionals were mainly "slightly confident" in their knowledge and use of insulin. Confidence level positively correlated to performance, but number of years' experience did not result in higher confidence or performance. This small-scale study allowed for a broad assessment of insulin-related topics that have been identified both nationally and locally as particularly problematic. Identifying knowledge gaps may help tailor strategies to help improve insulin knowledge and patient safety.